Integration of waqf and Islamic microfinance for poverty reduction: case studies of Malaysia, Indonesia and Bangladesh - Haneef, Mohamed Aslam; Pramanik, Ataul Huq; Mohamed, Mustafa Omar; Muhammad, Aliyu Dahiru; Amin, Fouad M (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2015)
This report presents the output of two-year collaboration between the Centre for Islamic Economics, IIUM and the Statistical, Economic, Social Research and Training Centre for Islamic Countries (SESRIC) on a research project that covered three OIC member countries namely, Malaysia, Indonesia and Bangladesh. The report briefly examines the poverty profile and poverty alleviation programs introduced in these countries. In doing so, the report explored the possibility of integrating the institutions of Waqf and microfinance as a model for poverty alleviation in the selected countries. Depending on the successful operation of this model in these three selected countries, this Integrated Waqf-based Islamic Microfinance (IWIM) model is expected to be replicated in other OIC member countries.